2008
DOI: 10.1161/atvbaha.107.160663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Statins on Adipose Tissue Inflammation

Abstract: Objectives-Macrophage-mediated chronic inflammation of adipose tissue is causally linked to insulin resistance in obesity. The beneficial effects of 3-hydroxy-3-methylglutaryl (HMG) coenzyme A (CoA) reductase inhibitors (statins) on glucose metabolism have been suggested, but the effects of these agents on adipose tissue inflammation are unclear.The aim of the present study is to define the effects of statins on adipose tissue inflammation and macrophages. Methods and Results-Pravastatin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 41 publications
4
38
1
Order By: Relevance
“…Adiponectin promotes HDL production via ApoA-I production and increased ABCA1 expression in the liver 77,78) , and also in macrophages to activate RCT 79) . Pitavastatin and pravastatin elevate adiponectin expression in adipocytes 80) . Clinically, the adiponectin-elevating effects differ among statins [81][82][83][84] , and pitavastatin reportedly increases adiponectin levels in hyperlipidemic patients with diabetes mellitus.…”
Section: Other Factors Involved In Rct 1) Adiponectinmentioning
confidence: 99%
“…Adiponectin promotes HDL production via ApoA-I production and increased ABCA1 expression in the liver 77,78) , and also in macrophages to activate RCT 79) . Pitavastatin and pravastatin elevate adiponectin expression in adipocytes 80) . Clinically, the adiponectin-elevating effects differ among statins [81][82][83][84] , and pitavastatin reportedly increases adiponectin levels in hyperlipidemic patients with diabetes mellitus.…”
Section: Other Factors Involved In Rct 1) Adiponectinmentioning
confidence: 99%
“…0 primer-GACTGTACAAATCACGTTGGGA), and GAPDH (5 0 primer-TTGTCTCCTGCGACTTCA, 3 0 primer-CACCACC-CTGTTGCTGTA) were employed (28)(29)(30)(31). To assess the specificity of each primer set, amplicons generated from the PCR reaction were analyzed for melting curves and also by electrophoresis in 2% agarose gels.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
“…Abe et al (17) demonstrated that pravastatin did not increase plasma adiponectin levels although normal mice treated with pravastin did show such an increase. Adiponectin is an insulin sensitizing factor derived from adipocytes.…”
Section: Discussionmentioning
confidence: 99%